A review of paediatric cardiology outreach clinics. (29th September 2015) - Davis, A; Kelsall, W; Yates, R
Abstract : Background: Paediatric cardiology outreach clinics allow children with congenital heart disease (CHD) to be seen close to their home by visiting paediatric cardiologists, as recommended by the Kennedy Bristol Inquiry1 . The British Congenital Cardiac Association (BCCA) has published guidance for outreach clinics, outlining referral process and clinic size2 . The aim of this study was to review outreach clinic activity and determine whether BCCA recommendations were met. Method: Clinic letters and appointment history for each patient seen in the outreach clinic between June 2004 and June 2009 were reviewed to determine: reason for attendance; underlying diagnosis; prenatal diagnoses; number of appointments attended; outcome following last appointment attended and clinic size. Results: Over the 61-month study period, 489 patients were seen in the outreach clinic. 257 (53%) were male. 271 (56%) children were followed after surgical or catheter intervention; 167 (34%) children with CHD had not undergone any procedure and were monitored; 35 (7%) children attended for screening in view of family history; 12 (2%) children were reviewed with arrhythmias and 4 (1%) after Kawasaki's disease. The most common diagnosis was ventricular septal defect (113; 23%). 49 (10%) children were diagnosed antenatally with CHD. Overall 272 children (56%) are still seen in the outreach clinic. 15 (3%) are seen in the local paediatric cardiology clinic. 102 (21%) have been discharged; 42 (8%) were transferred to other centres; 42 (8%) were transferred to adult services; 8 (2%) died during the study period and 8 (2%) were lost to follow-up. There were 113 outreach clinics. The median number of patients attending was 14 (range: 7–19). 36 clinics (32%) exceeded the recommended maximum of 15 patients, while seven clinics (6%) had fewer than the recommended minimum of 10 patients. There were a total of 1415 appointments in the outreach clinic. The median number of appointments attended by each child was 2 (range: 1–23). Conclusion: The outreach clinic is well utilised by local families, reducing travel to specialist centres with significant financial benefit. All referrals made to the outreach clinic met BCCA guidance. A significant proportion of the outreach clinics were overbooked, which could have a detrimental effect on patient care. The workload following antenatal diagnosis remains small.